RESOLUTION OF TRADITIONAL CONFLICT BETWEEN KOMUNING TRADITIONAL VILLAGE AND BUDAGA TRADITIONAL VILLAGE IN KLUNGKUNG, BALI - Aryawan, I Ketut Wenten; Mertha, S.H.,M.Hum., Prof. Dr. I Ketut; Parimartha, M.A, Prof. Dr. I Gde; Dhana, M.A, Dr. I Nyoman (E-Journal of Cultural Studies; Vol 9, No 3 (2016): August 2016, 2016)
This present study discusses the traditional conflict between BudagaTraditional Village and Kemoning Traditional Village, Klungkung Regency, Bali Province. The study is intended to (1) find out the resolution of the traditional conflict between Kemoning Traditional Village and Budaga Traditional Village which was dominated by MajelisUtamaDesaPakraman (MUDP); (2) identify the mechanism through which the decision was made by MUDP to settle such a traditional conflict; (3) identify the implication of the settlement of such a traditional conflict on the relationship between Budaga Traditional Village and Kemoning TraditionalVillage after the decision was made by MUDP. This present study is also aimed at finding out the picture of such a conflict between the two traditional villages. The study used the qualitative method.  The data were collected through observation, interview, library research, and documentary study. The theoretical approach which includes the theory of hegemony, the theory of mediation, and the theory of deconstruction was also used. The result of the study shows that the local traditional law ‘awig-awigdesapakaraman’ could not always be used as a reference to settle the dispute between the two villages. Every attempt made by the MUDP in relation to the resolution which was proposed in the earlier stages was considered unfair. The mechanism through which such a conflict was settled was dominated by the MUDP and did not show any decision which reflected the principles of mediation. The implication of the settlement of such a conflict between the two traditional villages was that the relationship between them had not been in harmony.
Keywords: resolution, traditional conflict, traditional village